KEDUDUKAN HUKUM PERDAGANGAN INTERNASIONAL TERHADAP PEREKONOMIAN INDONESIA - Ni Kadek Srimasih Ristiyani; Ni Putu Rai Yuliartini (Jurnal Komunikasi Hukum, 2022)
International trade is trade carried out between countries or state governments with other countries undergoing a trade relationship in accordance with the agreement between the two parties conducting international trade. Trading international trade is trade carried out by residents of a country with residents of other countries by mutual agreement. The population in questions can be between individuals (individuals with individuals), between individuals and the government of a country, or the government of one country with the government of another country. By conducting international trade, it will provide benefits and make the country’s economic growth directly in the form of an influence on the allocation of resources or directly such as the number of investors entering. Intrernational is also important because it can help create jobs.